2022
DOI: 10.3389/feduc.2022.983055
|View full text |Cite
|
Sign up to set email alerts
|

Rubric development for AI-enabled scoring of three-dimensional constructed-response assessment aligned to NGSS learning progression

Abstract: IntroductionThe Framework for K-12 Science Education (the Framework) and the Next- Generation Science Standards (NGSS) define three dimensions of science: disciplinary core ideas, scientific and engineering practices, and crosscutting concepts and emphasize the integration of the three dimensions (3D) to reflect deep science understanding. The Framework also emphasizes the importance of using learning progressions (LPs) as roadmaps to guide assessment development. These assessments capable of measuring the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…To mitigate potential bias, researchers suggested both the deconstruction of holistic rubrics and reconstruction of analytic rubrics to singular levels, respectively, to ensure the rubric descriptors measure the intended aspects in a quantitative, measurable manner (Jescovitch et al, 2019; Martin and Graulich, 2023). Previous studies have shown the decomposition of holistic rubrics of multi-dimensional science CRs, which can be achieved by breaking down a holistic rubric into discrete conceptual components which form the basis of analytic rubrics, and be used with high interrater reliability (Kaldaras, Yoshida and Haudek, 2022). Conversely, other studies acknowledge the sophisticated construct implied by the holistic nature of assessment.…”
Section: Coding Framework Of Cr Assessmentmentioning
confidence: 99%
“…To mitigate potential bias, researchers suggested both the deconstruction of holistic rubrics and reconstruction of analytic rubrics to singular levels, respectively, to ensure the rubric descriptors measure the intended aspects in a quantitative, measurable manner (Jescovitch et al, 2019; Martin and Graulich, 2023). Previous studies have shown the decomposition of holistic rubrics of multi-dimensional science CRs, which can be achieved by breaking down a holistic rubric into discrete conceptual components which form the basis of analytic rubrics, and be used with high interrater reliability (Kaldaras, Yoshida and Haudek, 2022). Conversely, other studies acknowledge the sophisticated construct implied by the holistic nature of assessment.…”
Section: Coding Framework Of Cr Assessmentmentioning
confidence: 99%